Implementation of Gemini Application in Moral Education for Early Childhood Learning - Yonanda Afrilioni; Alimni Alimni; Dayun Riyadi (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2026)
Moral education in early childhood holds critical urgency, as this developmental stage represents the golden age that shapes children’s character, moral values, and spiritual foundations for subsequent growth. This study aims to analyze the implementation of the Gemini application in moral education for early childhood learning. Employing a qualitative case study design, data were collected from four classroom teachers and one principal through in-depth interviews using purposive sampling, with all students observed as research subjects to assess character development. Data were obtained through interviews and classroom observations, then analyzed using data reduction, presentation, and conclusion drawing techniques, with validity ensured through source and methodological triangulation. The findings reveal that the integration of the Gemini application occurs across planning, implementation, and material development stages, serving as a source of ideas, references, Islamic stories, and learning activities tailored to the characteristics of young children. The use of Gemini enhances efficiency in lesson preparation, strengthens teachers’ creativity in designing moral education, and provides more relevant learning materials aligned with early childhood needs. This study contributes to the growing discourse on artificial intelligence in moral education and offers practical insights for teachers to integrate the Gemini application effectively, creatively, and responsibly in early childhood education.